PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR GEOGRAFI PADA MATERI PEMANFAATAN LINGKUNGAN HIDUP KAITANNYA DENGAN PEMBANGUNAN BERKELANJUTAN DI SMA BATIK 1 SURAKARTA TAHUN AJARAN 2013/2014 - istikomah, istikomah (Pendidikan Geografi, 2013)
ABSTRACT The objective of this research are to investigate the improvement of quality of Geography learning process and learning result through the application of the Discovery Learning model on the topic of discussion of Environmental Utilization in Relation to Sustainable Development at Senior Secondary School Batik 1 of Surakarta in Academic Year 2013/2014. This research used the classroom action research with two cycles. The subjects of the research were the students in Grade XI of Social Science Program 4 of Senior Secondary School Batik 1 of Surakarta in Even Semester in Academic Year 2013/2014. Meanwhile, the objects of the research were Geography learning process and learning result on the topic of discussion of Environmental Utilization in Relation to Sustainable Development through the application of the Discovery Learning model. The data of the research were collected through in-depth interview, documentation, test, and questionnaire. They were analyzed by using the descriptive comparative and critical techniques of analysis. The results of the research are as follows: 1)The application of the discovery learning model can improve quality of Geography learning process and on the topic of discussion of ?Environmental Utilization in Relation to Sustainable Development? as indicated by the results of the learning implementation in Cycle I and II. In Cycle I, the percentage targeted is not achieved as it only reaches 68.75% out of at least 75%. However, in Cycle II, the percentage becomes 87.22%, exceeding the minimal requirement. 2) The application of the discovery learning model can improve the Geography learning result on the topic of discussion of ?Environmental Utilization in Relation to Sustainable Development? as signified by the results of the learning implementation in Cycle I and II. The percentage of the students who fulfill the minimal learning completeness criteria is 76.92 % in Cycle I, and it becomes 86.96 % in Cycle II. Keywords: Discovery learning, quality of learning process, and learning result